Robotic Extrusion of Algae‐Laden Hydrogels for Large‐Scale Applications. Issue 1 (11th November 2019) - Malik, Shneel; Hagopian, Julie; Mohite, Sanika; Lintong, Cao; Stoffels, Laura; Giannakopoulos, Sofoklis; Beckett, Richard; Leung, Christopher; Ruiz, Javier; Cruz, Marcos; Parker, Brenda
Abstract: A bioprinting technique for large‐scale, custom‐printed immobilization of microalgae is developed for potential applications within architecture and the built environment. Alginate‐based hydrogels with various rheology modifying polymers and varying water percentages are characterized to establish a window of operation suitable for layer‐by‐layer deposition on a large scale. Hydrogels formulated with methylcellulose and carrageenan, with water percentages ranging from 80% to 92.5%, demonstrate a dominant viscoelastic solid–like property with G′ > G″ and a low phase angle, making them the most suitable for extrusion‐based printing. A custom multimaterial pneumatic extrusion system is developed to be attached on the end effector of an industrial multiaxis robot arm, allowing precision‐based numerically controlled layered deposition of the viscous hydrogel. The relationship between the various printing parameters, namely air pressure, material viscosity, viscoelasticity, feed rate, printing distance, nozzle diameter, and the speed of printing, are characterized to achieve the desired resolution of the component. Printed prototypes are postcured in CaCl2 via crosslinking. Biocompatibility tests show that cells can survive for 21 days after printing the constructs. To demonstrate the methodology for scale‐up, a 1000 × 500 mm fibrous hydrogel panel is additively deposited with 3 different hydrogels with varying water percentages. Abstract : Algae‐laden hydrogels are 3D‐printed on a large scale through a custom‐built robotic extrusion system. Rheological characterization of alginate hydrogels identified physiochemical and biological properties suitable for 3D construction. Algal cells immobilized in CaCl2 survived extrusion, demonstrating the biocompatibility of the material and printing process. This work demonstrates potential for the design, fabrication, and scale‐up of photosynthetic membranes in architecture.